Independent midwifery practices in Cape Town: birth outcomes and predictors for medical interventions from 2003-2009 - Evans, Kristy (Department of Public Health and Family Medicine, 2024)
The midwifery model of care is a safe, effective, inexpensive, holistic, woman and baby cantered approach to maternal and infant health. It is widely used in developing and developed world contexts and has proven to have birth outcomes that are comparable to hospital-based, obstetric models. In many settings however, application of the independent midwifery model of care has become increasingly difficult to maintain. Tensions surrounding perceived skills and competencies of midwives, the increasing acceptance of hospital-based, obstetric models of childbirth, controversy over necessity and use of medical interventions, rising insurance premiums, and competition over clients in private sector scenarios are all factors contributing to both low availability and utilization in many countries, including South Africa. In order to consider the role of this model in maternity services in South Africa and to potentially make this model available on a wider scale, it is necessary to understand the demographics of current utilization of existing independent midwifery services, as well their as birth outcomes. This retrospective cohort study documents the total number of deliveries attended by independent midwives, the socio-demographic and reproductive characteristics of women using independent midwives and the birth outcomes and delivery types in the greater Cape Town region among the 16 independent midwives who have practiced during the six-and-a-half-year period of January 2003 - end of June 2009. It identifies factors associated with normal vaginal deliveries, instrumental deliveries and caesarean sections, as well as documents the socio-demographic and professional characteristics of the 16 independent midwives. Ethical approval for this research was granted by the University of Cape Town. Anonymous client data was collected from midwifery practices‟ Maternity Registers and transferred onto a data abstraction sheet. Midwife data was collected via an interviewer-administered questionnaire. All data was entered into Microsoft Excel and analyzed using Stata. The findings of this study will be used to inform maternal and infant health care policy, as well as provide statistics for independent midwives‟ quality assurance and auditing of services.